Bioactivity of selected South African medicinal plants used traditionally for the treatment and management of Neisseria gonorrhoeae - Tshikalange, T.E. (Thilivhali Emmanuel) (University of Pretoria, 2022)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2020.